(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aimed to determine the concept and importance of higher education system, clarifying the conceptual framework of corruption and definition of reforming . In addition, focusing on strategies of fighting the corruption in Iraq. And state how can activate the role of management in reforming higher education system. The research focus on two areas, the first area assigned to theoretical part according to books, articles, formal document, internet and studies related to the research, while the second area contains the applied part of the research through compare many aspects in national strategies issued by the associate council of fighting the corruption in Iraq for the years (2010-2014) and (2016-2020) higher education system, clarify results and discussion of the comparison. The research contains many conclusions and recommendation which help other researchers on giving confidence in effectiveness of the strategies that prepared to fighting the corruption and its possibility in fulfillment the higher education system requirements.